Perencanaan Sistem Pengangkutan Sampah Kecamatan Ngaliyan, Kota Semarang dengan Mengintegrasikan Analisis GIS dan Lalu Lintas - Arumdani, Indah Sekar; Sumiyati, Sri; Samadikun, Budi Prasetyo (Dampak, 2022)
Ngaliyan District, which is located in Semarang City, had a population of 162.622 in 2020, and its citizens multiply these couple of years. This rapid increase in population complies with waste production. However, the total amount of waste in 10 garbage dumps that go to the waste landfills is only 103,6 m3/day from the total amount of 270,98 m3/day. As a result, the percentage of waste transportation services in Ngaliyan District is only 32,8%. This phenomenon can occur because some garbage dumps have excessive generations. This study aims to plan an optimal waste transportation system so that costs incurred are more efficient. The condition of the road, traffic, and vehicle's speed of the waste transportation routes can influence the waste transportation time. Optimization method were using traffic counting and Network Analyst in GIS application. The lowest degree of road’s saturation at 05.00 - 12.00, which was the optimal transportation time. The optimal vehicle speed was gained from the degree of saturation, which was 49.8 km/hour, so the number of trips increases to 22 rits/day, with 18 containers and an average remaining working time of 2.11 hours. The percentage of the services increased to 62%, and the waste that went to the waste landfills become 168 m3. Vehicle operating costs that were calculated using the PIC method increased to IDR 1,870,555,843.46/ year. However, there was a decrease in the retribution cost to IDR 18,794/ family/ month because of the growth in the number of people served. Keywords: Optimization, waste transportation, GIS, traffic, vehicle operational costA B S T R A KKecamatan Ngaliyan yang terletak di Kota Semarang berpenduduk 162.622 jiwa pada tahun 2020, dan penduduknya berlipat ganda beberapa tahun ini. Pertambahan penduduk yang pesat ini sejalan dengan produksi sampah. Namun, total sampah di 10 TPA yang masuk ke TPA sampah hanya 103,6 m3 /hari dari total 270,98 m3 /hari. Akibatnya, persentase pelayanan pengangkutan sampah di Kecamatan Ngaliyan hanya 32,8%. Fenomena ini dapat terjadi karena beberapa tempat pembuangan sampah memiliki generasi yang berlebihan. Penelitian ini bertujuan untuk merencanakan sistem pengangkutan sampah yang optimal agar biaya yang dikeluarkan lebih efisien. Kondisi jalan, lalu lintas, dan kecepatan kendaraan pada jalur pengangkutan sampah dapat mempengaruhi waktu pengangkutan sampah. Metode optimasi menggunakan penghitungan trafik dan Network Analyst pada aplikasi GIS. Derajat kejenuhan jalan terendah pada pukul 05.00 - 12.00 merupakan waktu transportasi yang optimal. Kecepatan kendaraan optimal diperoleh dari derajat kejenuhan yaitu 49,8 km/jam, sehingga jumlah trip meningkat menjadi 22 rit/hari, dengan 18 peti kemas dan rata-rata sisa waktu kerja 2,11 jam. Persentase pelayanan meningkat menjadi 62%, dan sampah yang masuk ke TPA menjadi 168 m3 . Biaya operasional kendaraan yang dihitung dengan metode PIC meningkat menjadi Rp 1.870.555.843,46/tahun. Namun terjadi penurunan biaya retribusi menjadi Rp 18.794/KK/bulan karena pertumbuhan jumlah masyarakat yang dilayani. Kata Kunci: Optimalisasi, pengangkutan sampah, GIS, lalu lintas, biaya operasional kendaraan